2015
DOI: 10.1071/ch14117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modifying the Anion of an Ionic Liquid on the Outcome of an SN2 Process

Abstract: The effect of a series of ionic liquids containing different anions (bis(trifluoromethanesulfonyl)imide, dicyanimide, hexafluorophosphate, tetrafluoroborate, and bromide) on the rate constant of a bimolecular substitution process was investigated. A general ionic liquid effect was noted, with increases in the rate constant observed in all ionic liquids used when compared with that in acetonitrile. Temperature-dependent kinetic data allowed calculation of activation parameters in each of the reaction mixtures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 16 publications
5
56
1
Order By: Relevance
“…In conclusion, the favorability of the substitution and the elimination mechanistic pathways correlate strongly, though not completely, with the Kamlet-Taft solvatochromic parameters of the hydrogen bond donating and accepting ability of the ILs. It is interesting to note that this differs from the results found for bimolecular (S N 2) substitution reactions [10,11].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In conclusion, the favorability of the substitution and the elimination mechanistic pathways correlate strongly, though not completely, with the Kamlet-Taft solvatochromic parameters of the hydrogen bond donating and accepting ability of the ILs. It is interesting to note that this differs from the results found for bimolecular (S N 2) substitution reactions [10,11].…”
Section: Discussioncontrasting
confidence: 54%
“…Molecules 2016, 21, 60 2 of 8 IL anion [11] on SN2 reactivity. Their work has shown that the identities of both the IL cation and anion have little effect on the reaction outcome other than general electrostatic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,[16][17][18][19][20][21][22][23][24] The use of this method allows convenient analysis of this reaction 27 and circumvents any issues with work-up of the reaction mixture (such as selective extraction of components of the reaction mixture 16 ). 6,7,[16][17][18][19][20][21][22][23][24] The use of this method allows convenient analysis of this reaction 27 and circumvents any issues with work-up of the reaction mixture (such as selective extraction of components of the reaction mixture 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Blanch and Wentrup (University of Queensland) describe an investigation into fluorinated carbene reactive intermediates [1] ; Read and co-workers (UNSW) report on the synthesis of novel fluorous surfactant molecules [2] ; Chebib (University of Sydney) and co-workers describe the receptor binding properties of shape-controlled fluorinated GABA analogues [3] ; Matesic and co-workers (Australian Nuclear Science and Technology Organisation) publish a microfluidic protocol for the automated production of 18 F-labelled compounds [4] ; Fraser and Easton (ANU) review the state-of-the-art in biosynthesis approaches to fluorinated peptides and proteins [5] ; Gardiner (CSIRO) reviews the production and commercial applications of fluoropolymers [6] ; Patel and Liu (Macquarie University) describe the synthesis and conformational analysis of fluorinated N-heterocycles [7] ; Harper and co-workers (UNSW) report on the outcomes of S N 2 reactions performed in fluorinated ionic liquid media [8] ; Kassiou and co-workers (University of Sydney) report on the clandestine production of fluorinated recreational drugs [9] ; Hunter and co-workers (UNSW) describe an investigation of fluorinated proline derivatives as enantioselective organocatalysts [10] ; and in an international contribution to this issue, O'Hagan and co-workers (University of St Andrews, UK) report on the fluorovinyl thioether functional group as a novel potential bioisostere of thioester enolates. [11] I sincerely thank all of the authors who have made such fine contributions to this Research Front, as well as the editorial and administrative staff of Aust.…”
mentioning
confidence: 99%